POSITION OF ENTREPRENEURSHIP EDUCATION IN LITHUANIAN GENERAL EDUCATION CURRICULUM AND IN EDUCATIONAL PROCESS IN GENERAL EDUCATION SCHOOL - Prakapas, Romas; Žibėnienė, Gintautė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Entrepreneurship, as one of today’s most relevant competences, is widely discussed in the public space. We must admit that scientific discussions have not yet led to a unanimous definition of the phenomenon, although the studies themselves are quite abundant. On the other hand, considering the social reality as being subject to constant change, it is also important to analyse the documents which are directly related to change of content of the said education. Scientific problem can be set as follows: what entrepreneurship education is provided in today’s general education school of Lithuania. Purpose – toreveal position of entrepreneurship education in Lithuanian general education curriculum and in educational process in general education school. It analysed the regulations on the Lithuanian general school curriculum content of the school year 2016-2017 in terms of the development of entrepreneurship: strategies, curricula, resources, etc. The analysis shows that in terms of modelling of curriculum formal education is aimed at training entrepreneurship following the principles of holistic approach, integrity and consistency. Lithuanian general curricula for general education are modelled in such a way that the learners integrally understand entrepreneurship, from different perspectives of subjects, as an integral competence.